Epigenetic regulation of diabetogenic adipose morphology - A.G. Kerr; I. Sinha; S. Dadvar; P. Arner; I. Dahlman (Elsevier, 2019)
Objective: Hypertrophic white adipose tissue (WAT) morphology is associated with insulin resistance and type 2 diabetes. The mechanisms governing hyperplastic versus hypertrophic WAT expansion are poorly understood. We assessed if epigenetic modifications in adipocytes are associated with hypertrophic adipose morphology. A subset of genes with differentially methylated CpG-sites (DMS) in the promoters was taken forward for functional evaluation. Methods: The study included 126 women who underwent abdominal subcutaneous biopsy to determine adipose morphology. Global transcriptome profiling was performed on WAT from 113 of the women, and CpG methylome profiling on isolated adipocytes from 78 women. Small interfering RNAs (siRNA) knockdown in human mesenchymal stem cells (hMSCs) was used to assess influence of specific genes on lipid storage. Results: A higher proportion of CpG-sites were methylated in hypertrophic compared to hyperplastic WAT. Methylation at 35,138 CpG-sites was found to correlate to adipose morphology. 2,102 of these CpG-sites were also differentially methylated in T2D; 98% showed directionally consistent change in methylation in WAT hypertrophy and T2D. We identified 2,508 DMS in 638 adipose morphology-associated genes where methylation correlated with gene expression. These genes were over-represented in gene sets relevant to WAT hypertrophy, such as insulin resistance, lipolysis, extracellular matrix organization, and innate immunity. siRNA knockdown of ADH1B, AZGP1, C14orf180, GYG2, HADH, PRKAR2B, PFKFB3, and AQP7 influenced lipid storage and metabolism. Conclusion: CpG methylation could be influential in determining adipose morphology and thereby constitute a novel antidiabetic target. We identified C14orf180 as a novel regulator of adipocyte lipid storage and possibly differentiation. Keywords: Adipocyte, Epigenetics, Adipogenesis, Insulin resistance